2017
DOI: 10.7448/ias.20.1.21552
|View full text |Cite
|
Sign up to set email alerts
|

Universal antiretroviral therapy for HIV‐infected children: a review of the benefits and risks to consider during implementation

Abstract: Background: The 2016 World Health Organization (WHO) consolidated guidelines on the use of antiretroviral drugs for treating and preventing HIV infection, recommended to start all HIV-infected children on antiretroviral therapy (ART). Here, we explore the possible benefits and risks of implementing universal ART for all HIV-infected children and adolescents and outline some of the key considerations that led to the 2016 revision of WHO guidelines.Methods: We conducted a review of the published data from 2000 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
(78 reference statements)
0
21
0
1
Order By: Relevance
“…At database closure, 4% of children in care had still not initiated ART in 2016. As universal ART is scaling-up in accordance with 2017 WHO guidelines, there is an urgency to identify these children and initiate them on treatment as soon as possible [30].…”
Section: Discussionmentioning
confidence: 99%
“…At database closure, 4% of children in care had still not initiated ART in 2016. As universal ART is scaling-up in accordance with 2017 WHO guidelines, there is an urgency to identify these children and initiate them on treatment as soon as possible [30].…”
Section: Discussionmentioning
confidence: 99%
“…Since the massive ART scale-up availability in low-income countries, the rate of vertical transmission of HIV-1 infection has considerably decreased along with the number of HIV-1-related pediatric deaths. ART administration has a positive impact on a variety of clinical symptoms associated with HIV-1 infection in children [ 1 ]. However, ART provided during the chronic phase of HIV-1 infection in children has ameliorated, but not reversed, abnormal features of immune activation [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specific pathways which result in impaired growth are multifactorial, including undernutrition, chronic inflammation, opportunistic infections, gastrointestinal illnesses, and endocrine abnormalities [4]. Previous clinical trials and observational studies have demonstrated improvements in growth after initiation of antiretroviral treatment (ART), although gains have often not been as strong in adolescents as among younger children.…”
Section: Introductionmentioning
confidence: 99%